Portfólio para práticas integrativas e complementares para pessoa idosa - Alves, Mônica Rocha Rodrigues (2018)
The Complementary and Integrative Therapies constitute a current theme by its importance of promoting and preventing health by means of complementary methods by the need of developing tools that strengthen primary care, due to the population growth of the elderly and the scarcity of resources available for the care in sickness. Objectives: To evaluate the scientific publications about the Complementary and Integrative Therapies; to verify the social representations of the elderly on complementary and integrative therapies and draw up an informative portfolio of complementary and integrative practices from the social representations of the elderly. Method: This is an exploratory study of mixed approach and for the seizure of the symbolic dimensions of Complementary and Integrative Therapies. We used the Theory of Social Representations, characterized also as a methodological research. The following steps were followed: research on the topic in the literature with search in virtual libraries and national and international databases; situational survey about the knowledge of complementary and integrative therapies in different groups; integrative literature review on the topic addressed. Results and Discussion: The integrative review of literature was the first article and showed that the knowledge about complementary and integrative practices is relevant to its implementation in health systems. Its use should be encouraged by management and health professionals as important strategies of health care for the population that needs of public health care quality. The social representations about the Complementary and Integrative Therapies for the elderly was the second article and it became clear that they presented a positive positioning and related to the image of the socialized elderly, able to promote health, autonomy and self-knowledge of their needs. The elaboration of an informative portfolio on complementary and integrative therapies was the third step of this research, and this material was drawn up going through a rigorous process of development characterized by constant evaluation mechanisms on the part of its target audience: the elderly. It led to the use of language and illustrations clearer, objective and accessible for the elderly population. Conclusion: It is expected that the knowledge produced in this dissertation, and this portfolio will bring benefits to the area of gerontology through the dissemination of conducts and practices addressed, which will provide the healthy aging, autonomy and quality of life of the elderly, promoting the strengthening of the Policy on Complementary and Integrative Therapies in the Health Unic System. RESUMEN Las terapias complementarias e integradoras constituyen un tema actual por la importancia de promover y prevenir la salud por medio de métodos complementarios, por la necesidad de desarrollar herramientas que fortalezcan la atención primaria, debido al crecimiento de la población de la tercera edad y la escasez de recursos disponibles para la atención en la enfermedad. Objetivos: Evaluar las publicaciones científicas acerca de las Terapias Complementarias e Integradoras; verificar las representaciones sociales de los ancianos en las terapias complementarias e integradoras y elaborar una cartera de informativos complementarios y prácticas integradoras de las representaciones sociales de los ancianos. Método: Este es un estudio exploratorio de enfoque mixto y la comprensión de las dimensiones simbólicas de terapias complementarias e integradoras. Hemos utilizado la teoría de las representaciones sociales, caracterizada también como las investigaciones metodológicas. Los siguientes pasos fueron seguidos: investigación acerca del tema en la literatura con la búsqueda en las bibliotecas virtuales y bases de datos nacionales e internacionales; encuesta situacional de los conocimientos acerca de las terapias complementarias e integradoras en diferentes grupos; Integradora de revisión de literatura acerca del tema. Resultados y Discusión: El Examen Integrador de la Literatura fue el primer artículo y reveló que los conocimientos acerca de las prácticas integradoras y complementarias es pertinente para su aplicación en los sistemas de salud. Su uso debe ser alentado por la administración y los profesionales de la salud como estrategias importantes de atención de la salud de la población que necesita de la atención de la salud pública de calidad. Las representaciones sociales acerca de las Terapias Complementarias e Integradoras para los ancianos fue el segundo artículo y quedó claro que presentan una posición positiva y relacionada con la imagen de los ancianos socializados, capaz de promover la salud, la autonomía y el conocimiento de sus necesidades. La elaboración de una cartera de informativos y terapias complementarias integradora fue la tercera etapa de esta investigación y este material fue elaborado, pasando por un riguroso proceso de desarrollo, caracterizados por mecanismos de evaluación constante por parte de su público objetivo: los ancianos, lo que condujo al uso del lenguaje y las ilustraciones más clara, objetiva y accesible para la población de edad avanzada. Conclusión: Se espera que el conocimiento producido en esta tesis y esta cartera traerá beneficios para el área de la gerontología a través de la difusión de conductas y prácticas dirigidas, que proporcionará el envejecimiento saludable, la autonomía y la calidad de vida de los ancianos, promover el fortalecimiento de la política sobre terapias complementarias e integrador en el Sistema Único de Salud.